Logical system of development economics of large countries. Issue 2 (2nd December 2019) - Ouyang, Yao
Abstract : Purpose: The development economics of large countries is a subject that studies how large developing countries evolve into developed countries through industrialization and structural transformation. By looking into the economic development of large developing countries in a systematic way, the purpose of this paper is to propose a logical system consisting of research objects, main issues, key principles and development strategies. Design/methodology/approach: A large developing country refers to a country with a dual economic structure; it has a large population, vast territory and great market potential, but is low in labour productivity and per capita income. Findings: The key issue of the large country's economy is the issue of the size, while the key issue of the developing country's economy is the issue of the economic structure. Therefore, the key issue of the economy of large developing courtiers lies in both the size and economic structure. Originality/value: The endogenous capacity of a large country depends on the size of factors and the balance of supply and demand, while the comprehensive advantage of a large country depends on its diversified industrial structure and integration of factors. Based on the basic characteristics and key economic principles, large developing countries should seek endogenous, stable, coordinated and innovative development.